4S consideration (synthesis, sonication, surfactant, stability) for the thermal conductivity of CeO2 with MWCNT and water based hybrid nanofluid: An experimental assessment - Tiwari, Arun Kumar; Pandya, Naimish S.; Said, Zafar; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier, 2021)
The main objective of the present study is to investigate the impact of nanofluid stabilization techniques (hybrid stabilization approach, i.e., a combination of different mechanical and chemical methods) on the stability and thermal conductivity of CeO2+MWCNT (80:20)/water based hybrid nanofluid. The nanofluid has been prepared by using the two-step method, and a broad range of ultrasonication time (30, 60, 90, 120, 150, and 180 min) has been used. Furthermore, different kinds of charged surfactants, two anionic (sodium dodecyl benzene sulfonate (SDBS), sodium dodecyl sulphate (SDS)), two cationic (cetyltrimethylammonium bromide (CTAB), distearyl dimethylammonium chloride (DDC)), and two polymers (gum Arabic (GA), PVP (polyvinyl pyrrolidone)) have been added to the base fluid with a different nanoparticle to surfactant mixing ratios (5:0, 4:1, 3:2, 2:3 and 1:4). The prepared samples were investigated at different pH values and different preparation days (15th, 30th, 45th,60th and 90th day) to evaluate which surfactant and mixing ratios are sufficient to achieve a stable nanofluid for more than 90 days. The observed optimum volumetric mixing ratio of surfactant and CeO2+MWCNT nanoparticle, pH level and sonication time are around 3:2, 9.5, and 90 min, respectively, for which hybrid nanofluid yields maximum zeta potential value as an indicator of nanofluids long term stability. The results of zeta potential analysis indicated that CTAB surfactant shows the best impact up to the 30th day from preparation, after the 30th day, the SDBS surfactant shows the highest degree of stability of the hybrid nanofluid applying 3:2 mixing ratio and 90 min sonication. Results clearly showed that the nanofluid hybrid stabilization approach has a strong relation with thermal conductivity. The addition of higher amounts of surfactant (more than 3:2 mixing ratio) caused a small thermal conductivity reduction. Additionally, precise assessments of the surfactant effect on a hybrid nanofluid's surface tension have also been studied. Finally, a correlation to predict the experimental value of thermal conductivity has been proposed from the experimental data, which could be beneficial for various heat transfer applications.
Keywords: Hybrid nanofluid; Thermal conductivity; pH; Stability; Surfactant; Sonication time